2005
DOI: 10.1007/s10350-004-0803-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized Trial Comparing Intraoperative Colonic Irrigation With Manual Decompression Only for Obstructed Left-Sided Colorectal Cancer

Abstract: Manual decompression of proximal colon without irrigation is as safe as colonic irrigation in one-stage surgical management of obstructing left-sided colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 19 publications
1
36
1
4
Order By: Relevance
“…There is one RCT comparing ICI with manual decompression in acute left-sided colonic obstruction. 21 It concluded that manual decompression is as good as ICI with no difference in morbidity or mortality, and it is a shorter and simpler procedure. Other non-randomised studies or case series have shown manual decompression to be safe.…”
Section: Primary Resectionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is one RCT comparing ICI with manual decompression in acute left-sided colonic obstruction. 21 It concluded that manual decompression is as good as ICI with no difference in morbidity or mortality, and it is a shorter and simpler procedure. Other non-randomised studies or case series have shown manual decompression to be safe.…”
Section: Primary Resectionmentioning
confidence: 98%
“…[18][19][20][21] This idea was supported by various RCTs comparing mechanical bowel preparation, with no preparation in elective open colonic surgery. The results were separately examined in a Cochrane systematic review of 9 RCTs 22 and in a metaanalysis of 7 RCTs.…”
Section: Primary Resectionmentioning
confidence: 99%
“…(2005), в котором проводится сравнение сег-ментарной колэктомии с интраоперационной иррига-цией (n = 24) и сегментарной колэктомии с мануальной декомпрессией (n = 25) при обтурационной кишечной непроходимости опухолевого генеза. Авторы пришли к выводу, что мануальная декомпрессия является ме-нее продолжительной по времени и технически проще в исполнении, статистической разницы в послеопе-рационной летальности и частоте несостоятельности анастомоза не выявлено [58]. В 2009 г. M. H. Kam и соавт.…”
Section: Introductionunclassified
“…Preoperative chemoradiotherapy (CRT) is strongly associated with poor anal function after ISR, and patients with rectal cancer who undergo ISR after preoperative CRT are likely to experience incontinence [11,12]. Lim et al [13] reported that a conventionally fractionated 45-Gy dose of preoperative CRT caused poor anorectal function due to damage to the pudendal nerve. Rectal function may also be worsened by radiation-induced proctitis and induction of rectal compliance due to fibrosis of the rectal wall [14,15].…”
Section: Introductionmentioning
confidence: 99%